Investigation of tidal grounding line migration using SAR line-of-sight offset time series - Ramanath Tarekere, Sindhu; Krieger, Lukas; Floricioiu, Dana; Wuite, Jan (2024)
Grounding lines (GLs) are subsurface geophysical features that represent the boundary between grounded ice and floating ice shelves. GLs derived from tidal remote sensing methods such as Differential Interferometric SAR, laser and radar altimetry contain an ephemeral displacement in addition to their true location. Previous works have demonstrated that grounding lines migrate with distances ranging from a few hundred meters to several kilometers heterogeneously and out of phase with ocean tides, implying that the tidal component does not diminish in an interannual time series. We explore the use of SAR line-of-sight (LOS) offsets to provide insights into tidal migration of the grounding line. We used a times series from 2019 - 2021 of LOS offsets from 6-day repeat cycle Sentinel-1 acquisitions over Larsen C Ice Shelf. We derived an average GL for each year by correlating the offsets with modelled tide amplitudes and tracked GL movement along several flowlines across the ice shelf.